Mobile Apps as Health-Supporting Tools in the Digital Era − Technological, Health, and Social Aspects of m-Health - Tabak, Nina; Olszar, Agata; Książek, Ewelina; Bochniak, Marta (Aplikacje mobilne jako narzędzia wspierające zdrowie w erze cyfrowej − technologiczne, zdrowotne i społeczne aspekty m-Health, 2024)
Aim: The aim of this article was to provide a comprehensive review of the technological, health, and social aspects of using m-Health apps. The article examines the potential benefits and challenges associated with their implementation and highlights future research directions to facilitate the effective integration of these technologies into the healthcare system. Methodology: A literature review was employed as the primary research method. Publications and reports concerning the rapid development of mobile technologies were analyzed, particularly emphas-izing the increasing number of applications supporting health monitoring and daily healthcare. Results: The analysis revealed that, with technological progress, mobile devices have become an integral part of daily life, contributing to a significant increase in mobile applications, including m-Health apps. These applications are gaining popularity due to their capabilities in monitoring health parameters and supporting preventive measures. It was also found that many of these applications remain under-developed despite the dynamic market growth, and their quality is not sufficiently validated. Implications and recommendations: The study’s findings indicate an urgent need to implement more rigorous standards for the evaluation and validation of m-Health applications, as well as to intensify research on the integration of digital technologies with the healthcare system to ensure their effectiveness, safety, and functional personalization. Originality/value: This work constitutes an original contribution to the field of digital health by providing a comprehensive synthesis of technological, health, and social issues related to m-Health applications. The article identifies key gaps in the quality and validation of these tools while outlining directions for future research and recommending practical solutions for more effective integration of mobile technologies into the healthcare system.
Nauki Inżynierskie i Technologie = Engineering Sciences and Technologies, 2024, Nr 40, s. 72-85
Keywords: m-health; mobile apps; health monitoring; healthcare system; health technologies; aplikacje mobilne; monitorowanie zdrowia; system opieki zdrowotnej; technologie zdrowotne